HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN KECEMASAN SOSIAL SISWA KELAS V SDN 31 SAIYUNG - Nugroho, Zikri; Anika Marhayani, Dina; Kusuma Wijaya, Andika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: 1) describe the level of self-confidence of class V students at SDN 31 Saiyung; 2) to describe the level of social anxiety of fifth grade students at SDN 31 Saiyung; 3) to describe the relationship between self-confidence and social anxiety in class V at SDN 31 Saiyung. The research used is correlation or relationship research with a quantitative approach. The population in this study were all class V students at SDN 31 Saiyung with a total of 33 students. The sampling technique used was the total sampling technique. Data collection techniques use non-test techniques. The non-test technique is in the form of a questionnaire sheet on students' self-confidence and social anxiety. Data were analyzed using normality tests and hypothesis testing using the product moment correlation test; The research results show that: (1) students' self-confidence is in the very good category with an average score percentage of 85.24%; (2) students' social anxiety is in the very high category with an average percentage score of 94.85%; (3) there is a relationship between students' self-confidence and students' social anxiety in class V of SDN 31 Saiyung, with a correlation coefficient of 0.455 in the very strong category. Student self-confidence provides a determinant coefficient of 20.7% for student social anxiety. Thus, it can be concluded that the higher the student's self-confidence, the lower the social anxiety experienced by the student, and conversely, the lower the student's self-confidence, the higher the social anxiety the student faces.